Peer Teaching for Early Reading of Elementary School Students: Classroom Implementation and Challenges - Pradini Wulan Safitri; Fitri Puji Rahmawati (Lembaga Penelitian dan Pengabdian kepada Masyarakat, 2023)
Reading is one of the crucial aspects in an educated society. However, in the process, students often face challenges or difficulties in learning to read and rarely receive attention from teachers. The purpose of this study was to analyze and describe the application of the peer teaching learning method to students' beginning reading skills. The research method used is qualitative research with exploratory descriptive design. Sources of data in this study were students and teachers in first grade of elementary school who had implemented the peer teaching learning method. Data collection techniques using documentation, interviews, and observation. Data analysis techniques used are data reduction, data display, and data verification. Test the validity of the data using technical triangulation. The results showed that the inclusion of students' initial reading skill aspects included being able to pronounce letters very fluently with no errors, being able to compose letters into words fluently even though there were a few structuring errors, understanding the meaning of words that were read quite fluently because there were several deficiencies in understanding the meaning of words, showing appropriate reading behavior quite fluently, there was activity of repeating words in reading even though not many words were repeated, and activities in decapitation were not quite right there were few errors, so that overall the coverage of reading skills through the peer teaching method analyzed was as large as fulfilling If the criterion is sufficient, in the future it is hoped that there will be a review related to the implementation of learning plans through the peer teaching method so that learning activities that refer to the development of students' reading abilities are achieved.